(untitled) (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2018)
Robin G. Collingwood is considered the great researcher of RomanoBritish studies in the interbellum period. His contributions in this field, although less famous than his works in the Philosophy of History, succeeded in inserting Roman Britain into British history, and brought in tow a unique interpretative approach that weaves philosophical and historical concepts with his archaeological research on the phenomenon of the "Romanisation" of the Roman provinces. His belief in the inevitability of the scholar’s prejudice in approaching his object and in his/her need and possibility to recreate the past in his/her own mind, in the present, has given Collingwood a kind of bibliographic renaissance in post-processual archaeological production. Somehow connected to this, his conception of "Romanisation," however rigid, is indelible to the epistemological critique of the term in British postcolonialism. Collingwood’s legacy usually oscillates between the reverential and the ridiculous, something that only reinforces the importance of such longlived movements.